Comparison and prognostic analysis of focal segmental glomerulosclerosis patients with or without nephrotic syndrome at onset - Liangliang Chen; Yanhong Ma; Xiaohan Huang; Junni Wang; Xiaoli Lin; Fanghao Cai; Huijing Wang; Huanhuan Zhu; Lan Lan; Pingping Ren; Jianghua Chen; Fei Han (BMC Nephrology)
Abstract Background Focal segmental glomerulosclerosis (FSGS) constituted one of the most common causes of end-stage kidney disease. We aimed to compare the presentation and prognosis for FSGS patients based on whether they met the criteria of nephrotic syndrome (NS) at disease onset. Methods Retrospective analysis of 291 treatment-naïve adult FSGS patients managed per clinical guidelines. Patients were categorized into non-NS-FSGS (n = 158) and NS-FSGS (n = 133) groups based on NS criteria. Immunosuppressants were administered based on KDIGO 2021 Guideline and disease progression. Kidney outcomes were analyzed in 144 patients followed up for more than 1 year. Results A total of 291 FSGS patients were included, with 158 patients in the non-NS-FSGS group and 133 patients in NS-FSGS group. Patients in the non-NS-FSGS group exhibited higher prevalences of hypertension, along with higher body mass index, hemoglobin level, eGFR, serum albumin and immunoglobulin levels, and more severe chronic pathological changes compared to those in NS-FSGS group. Among patients followed up for more than 1 year, the annual eGFR decline rate (ADR) was 5.0 (2.4, 10.1) % in the non-NS-FSGS group and 2.1 (0.6, 6.1) % in NS-FSGS group (P = 0.922); ADR > 5% was more common in non-NS-FSGS patients than in NS-FSGS patients (49.3% vs. 29.0%, P = 0.017), especially than treatment-responsive patients in the NS-FSGS group (49.3% vs. 17.2%, P < 0.001). For the non-NS-FSGS group, multivariate Cox regression revealed that persistent urinary protein-creatinine ratio (uPCR) ≥ 0.5 during follow-up (HR 2.455, 95% CI 1.105–5.454, P = 0.027) was an independent risk factor for ADR > 5%. Conclusions FSGS patients without NS at onset experienced a faster decline in kidney function compared to those with NS, particularly those with treatment-responsive NS.